The Development of Enteral Feeding for Home-Use Patients - Patipan Laokor; Dusit Suksawat; Nutthanan Wanluk; Jeerawan Thanarak; Chow Chompoo‐inwai (My University, 2025)
With the rising number of bedridden patients, affordable and accessible enteral feeding solutions are urgently needed. The high costs of imported feeding systems remain a burden for caregivers, especially in developing regions. This study presents the development of a cost-effective enteral feeding controller that utilizes a unique four-lobe camshaft mechanism, compatible with locally manufactured feeding bags. The redesigned mechanical structure focuses on simplifying the feeding operation while reducing overall device weight. The upgraded electronic control system, combined with a TFT LCD touchscreen, enhances usability. Performance testing demonstrated consistent flow rate accuracy at various levels and showcased the mechanical efficiency of the camshaft-driven feeding system. The successful outcomes of this project have led to commercial interest from a domestic medical device manufacturer, indicating readiness for standardization and mass production.
Keywords: Engineering and Technology Innovations; Infant Health and Development